Factors associated with alien plant richness, cover and composition differ in tropical island forests. Issue 12 (18th September 2019) - Ibanez, Thomas; Hart, Patrick; Ainsworth, Alison; Gross, Jacob; Monello, Ryan
Abstract: Aim: To examine how native plant native communities, environment and geography are associated with alien plant species invasion in tropical island forests. Location: Four US national parks in Hawai'i and American Samoa. Methods: We analysed the richness, coverage and composition of alien plant species communities located across 204 plots, five islands and two archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the relative importance of native plant species communities (richness, structure and composition), environment (temperatures, precipitation, and soil age) and geography (elevation, geographical distance between plots, identity of islands and archipelagos) on alien plant species communities. Results: Alien plant species were found in >90% of plots with on average four species covering ~15% of the understorey. Variation in alien species richness and coverage was primarily explained by archipelago and island identity and elevation. Plots located on younger islands tended to exhibit higher richness and coverage of alien plants. Native tree density and canopy height were negatively correlated with alien species coverage but not with alien species richness. Elevation was negatively correlated with both the richness and coverage of alien species. Differences in elevation, mean annual precipitation and geographical distances explained about 40% of the observed spatial turnover in alien species composition with differences in elevation being the main driver. Turnover in alien species composition was weakly correlated with turnover in native species. Main conclusions: In the studied islands, higher elevations seem to be relatively spared from alien species invasion so far. However, our results suggest that the negative effect of elevation on alien species coverage may be larger than on alien species richness. Maintenance of tall and dense canopy may limit the coverage of alien species but not the number of alien species. Our results also support that alien species invasion may be particularly high on isolated archipelagos and younger islands.